Exploring learners' satisfaction and dissatisfaction towards ICT Competency MOOC via critical incident technique (CIT) approach - Muhammad Haziq, Roslan (Universiti Malaysia Sarawak (UNIMAS), 2019)
Massive Open Online Courses or MOOCs are online course focusing on a large number of participants as well as open access via the web. For semester 1, 2018/2019, UNIMAS has employed fully online learning for ICT Competency course. As the implementation of this learning method is new, this study was conducted in order to explore learners' satisfaction and dissatisfaction towards ICT Competency MOOC via critical incident technique (CIT). This study also looked into the similarities and differences of the satisfaction and dissatisfaction factors among the learners of different genders and course performance. The satisfaction and dissatisfaction factors of the learners were categorized based on eightdimensional e-learning framework proposed by Badrul Khan which are pedagogical, technological, interface, evaluation, management, resource support, ethical and institutional. Data on learners' satisfaction and dissatisfaction was obtained by interviewing the learners, who took ICT Competency on semester 1, 2018/2019. It could conclude that most of the informants satisfied with the technological, pedagogical, evaluation and interface aspects of ICT Competency MOOC. However, the informants dissatisfied with pedagogical, ethical, engagement with lecturer and management aspects of ICT Competency MOOC. The result displayed that each criteria of eight-dimensional e-learning framework play vital role to ensure the learners' satisfaction while enrolling in the course. Thus, satisfying the learners is important to ensure the continuity of the implementation of MOOC on ICT competency course in UNIMAS.